Early-strength corrosion-resistant aluminoferrite cement-based concrete and preparation method thereof

By adding temperature-sensitive water-reducing polycarboxylic acid water-reducing agent, temperature-sensitive slump-reducing polycarboxylic acid water-reducing agent and internal curing nano-plant fiber emulsion to the iron aluminate cement concrete, the problems of poor construction properties and temperature cracks of concrete are solved, and the early strength and corrosion resistance are improved.

CN119874303AActive Publication Date: 2025-04-25CCCC FOURTH HARBOR ENG INST CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411992107.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing iron aluminate cement concrete has poor construction properties during construction and is prone to temperature cracks. The early hydration and heat concentration leads to rapid fluid loss.

Method used

Early-strength corrosion-resistant iron aluminate cement-based concrete is used, and the hydration process and concrete properties are regulated by adding temperature-sensitive water-reducing polycarboxylic acid water-reducing agent and temperature-sensitive slump-reducing polycarboxylic acid water-reducing agent, combined with internal curing nanoplant fiber emulsion.

Benefits of technology

Improves the and ease of concrete, reduces viscosity, delays hydration and exothermic, improves early strength and crack resistance, and reduces the risk of temperature cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874303A_ABST
    Figure CN119874303A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to early-strength corrosion-resistant aluminoferrite cement-based concrete and a preparation method thereof. The early-strength corrosion-resistant aluminoferrite cement-based concrete is prepared from the following raw materials in parts by weight: 280 to 400 parts of aluminoferrite cement, 0 to 70 parts of fly ash, 0 to 85 parts of mineral powder, 0 to 20 parts of silicon powder, 670 to 750 parts of sand, 1100 to 1150 parts of gravel, 150 to 165 parts of water, 3 to 6 parts of special water reducing agent for aluminoferrite cement concrete and 0.6 to 1.2 parts of internal curing nano plant fiber emulsion. The concrete is prepared by doping a special water reducing agent and an internal curing material into the aluminoferrite cement, and the hydration of the aluminoferrite cement and the adsorption of the additive are synergistically regulated, so that the workability of the aluminoferrite cement concrete can be improved, and the viscosity of the concrete is reduced; and the concrete can improve the slump gradual retentivity, reduce the early hydration heat release, enhance the early mechanical properties, crack resistance and durability of the concrete, and can be widely applied to marine foundation engineering such as ports, wharfs, cross-sea bridges and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to an early-strength corrosion-resistant ferroaluminate cement-based concrete and a preparation method thereof. Background Art

[0002] Marine infrastructure faces severe corrosion from seawater. In order to ensure the long life of marine infrastructure, higher challenges and requirements will be put forward for engineering cement-based materials. Ferroaluminate cement is the third series of cement independently developed by my country. It is a hydraulic cementitious material made by calcining raw materials to obtain clinker with anhydrous calcium sulfoaluminate, iron phase and dicalcium silicate as the main components, adding appropriate amount of gypsum and 0% to 10% limestone. It has excellent properties such as fast hardening, early strength, corrosion resistance, freeze-thaw resistance, and impermeability. Due to the excellent early strength and corrosion resistance of ferroaluminate cement concrete, its use in marine infrastructure with severe corrosion can significantly improve the service life of the building.

[0003] Patent CN117447166A discloses "A low hydration heat and large volume alumina ferrocement concrete and its preparation method", which adopts low hydration heat and large volume alumina ferrocement concrete with low hydration heat, large amount of ultrafine admixture grading, reasonable sand, stone aggregate, cold water mixing, premixed mortar method and other measures to prepare a low hydration heat and large volume alumina ferrocement concrete; Patent CN117447168A discloses "A low viscosity and high durability alumina ferrocement concrete and its preparation method", whose formula mainly involves alumina ferrocement, steel slag powder, viscosity-reducing modified material, sand, gravel, water reducer, water, and adopts premixed mortar method and post-addition of gravel method to prepare low viscosity and high durability alumina ferrocement concrete; Patent CN116354680A discloses "A high crack resistance and high corrosion resistance marine engineering concrete and its preparation method", which proposes to use modified internal curing materials including internal curing agent, graphene nanosheets and binder to alleviate the problem of early heat concentration of alumina ferrocement concrete, reduce the temperature difference between the inside and outside of concrete, and thus reduce temperature cracks.

[0004] However, in actual engineering applications, the alumina ferroaluminate cement concrete has high early strength and reacts quickly with anhydrous calcium sulfoaluminate in its components. Therefore, the cement releases a large amount of heat in the early stage and the heat release is concentrated, which can easily lead to the following problems: 1. The alumina ferroaluminate cement has poor compatibility with ordinary polycarboxylic acid high-performance water-reducing agents, and is prone to problems such as high cohesion; 2. The concrete loses fluidity quickly and is sensitive to the temperature of the construction environment, which affects the on-site concrete construction; 3. The internal insulation temperature of the alumina ferroaluminate cement concrete structure rises, which can easily cause temperature cracks. Summary of the invention

[0005] The main purpose of the present invention is to provide an early-strength corrosion-resistant alumina-ferrocement-based concrete and a preparation method thereof, aiming to improve the technical problems of the existing alumina-ferrocement concrete, such as poor workability and easy generation of temperature cracks.

[0006] To achieve the above-mentioned purpose, the present invention provides an early-strength corrosion-resistant ferroaluminate cement-based concrete, which comprises the following raw materials, by weight: 280-400 parts of ferroaluminate cement, 0-70 parts of fly ash, 0-85 parts of mineral powder, 0-20 parts of silica fume, 670-750 parts of sand, 1100-1150 parts of crushed stone, 150-165 parts of water, 3-6 parts of special water reducer for ferroaluminate cement concrete and 0.6-1.2 parts of internal curing nano-plant fiber emulsion.

[0007] Preferably, the special water reducer for ferroaluminate cement concrete includes the following raw materials, measured by weight: 8 to 12 parts of temperature-sensitive water-reducing polycarboxylate water reducer, 8 to 12 parts of temperature-sensitive slump-retaining polycarboxylate water reducer, 0 to 6 parts of retarder, 70 to 84 parts of water, 0.02 to 0.05 parts of defoamer, 0.02 to 0.06 parts of air entraining agent and 0.1 to 0.2 parts of preservative.

[0008] Preferably, the preparation steps of the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive collapse-retaining polycarboxylate water-reducing agent include:

[0009] S1. Preparation of unsaturated alkane amino amide intermediate: 74 to 102 parts of saturated alkane diamine and 13.5 to 17.5 parts of water-carrying agent are mixed and stirred evenly, and then 0.75 to 1.00 parts of catalyst are added, and then the temperature is raised to 90 to 105° C., 75 to 90 parts of unsaturated carboxylic acid are added, and the temperature is kept for 2 to 4 hours until no water is generated, and the temperature is lowered to below 40° C. and 37 to 48 parts of baking soda solution with a concentration of 5 to 10% are added to terminate the amidation reaction to obtain an unsaturated alkane amino amide intermediate;

[0010] S2. Preparation of a thermosensitive water-reducing polycarboxylate water reducer: 24 to 26 parts of the unsaturated alkane amino amide intermediate, 235 to 245 parts of a polyoxyethylene ether macromonomer and 10 to 20 parts of water were mixed and stirred evenly, heated to 30 to 60 ° C, 14 to 16 parts of an oxidant were added, and then solution A and solution B were added dropwise thereto in sequence, and finally 13 to 15 parts of a sodium hydroxide solution having a concentration of 28 to 35% was added, and the pH value was adjusted to 6.0 to 7.0 to obtain a thermosensitive water-reducing polycarboxylate water reducer;

[0011] S3. Preparation of a temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent: 25 to 26 parts of the unsaturated alkane amino amide intermediate, 240 to 250 parts of polyoxyethylene ether macromonomer and 20 to 30 parts of water are mixed and stirred evenly, the temperature is raised to 30 to 60°C, 15-16 parts of an oxidant are added, and then liquid A and liquid B are added dropwise thereto in sequence, and finally 15 to 16 parts of a 28 to 35% sodium hydroxide solution is added, and the pH value is adjusted to 6.0 to 7.0 to obtain a temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent.

[0012] Preferably, in step S1, 75 to 90 parts of the unsaturated carboxylic acid are added in three portions, with 1 / 3 of the total amount of the unsaturated carboxylic acid added every 1.5 hours until the addition is complete;

[0013] The saturated alkane diamine is one of 1,2-propylene diamine and 2-methyl-1,2-butane diamine; the unsaturated carboxylic acid is one of acrylic acid and methacrylic acid; the water-carrying agent is cyclohexane; and the catalyst is one of concentrated sulfuric acid and p-toluenesulfonic acid.

[0014] Preferably, in step S2 or step S3, the polyoxyethylene ether macromonomer is one of allyl polyoxyethylene ether or methyl allyl polyoxyethylene ether; and the oxidant is one of hydrogen peroxide or ammonium persulfate.

[0015] Preferably, in step S2, the liquid A is composed of 18 to 22 parts of unsaturated carboxylic acid and 15 to 20 parts of water, by weight; the liquid B is composed of 0.4 to 0.5 parts of reducing agent, 1.5 to 3 parts of chain transfer agent and 30 to 40 parts of water, by weight, and the time for completing the dropwise addition of the liquid A is 2 to 3 hours, and the time for completing the dropwise addition of the liquid B is 2.5 to 3.5 hours;

[0016] In step S3, the liquid A is composed of 10 to 12 parts of unsaturated carboxylic acid, 35 to 39 parts of collapse-preserving functional monomers and 40 to 50 parts of water, by weight; the liquid B is composed of 0.4 to 0.5 parts of reducing agent, 2 to 3 parts of chain transfer agent and 30 to 40 parts of water, by weight, and the time for completing the dropwise addition of the liquid A is 2 to 3 hours, and the time for completing the dropwise addition of the liquid B is 2.5 to 3.5 hours;

[0017] In step S2 or step S3, the unsaturated carboxylic acid is one of acrylic acid or methacrylic acid; the reducing agent is vitamin C; the chain transfer agent is one of thioglycolic acid or thiopropionic acid; in step S3, the collapse-preserving functional monomer is one of hydroxyethyl acrylate or hydroxypropyl acrylate.

[0018] Preferably, the retarder is one or two of sodium gluconate, boric acid, citric acid or sodium phosphate; the defoamer is a polyether defoamer or a silicone defoamer; the air entraining agent is a mixture of a rosin soap air entraining agent and a fatty alcohol sulfonate air entraining agent in a weight ratio of 1:0.5-2; and the preservative is an isothiazolinone preservative.

[0019] In addition, the present invention also proposes a method for preparing the above-mentioned early-strength corrosion-resistant ferroaluminate cement-based concrete, comprising the following steps:

[0020] S01. Mix the ferroaluminate cement, the fly ash, the mineral powder, the silica fume, the sand and the gravel in parts by weight and stir for 10 to 15 seconds to obtain a premix;

[0021] S02. According to weight, the special water reducer for alumina ferroaluminate cement concrete and the internal curing nano-plant fiber emulsion are added to water and mixed evenly, and then added to the premix and stirred evenly to obtain the early strength and corrosion-resistant alumina ferroaluminate cement-based concrete.

[0022] Preferably, the strength grade of the alumino-ferrocement is not less than 42.5; in terms of mass percentage, the Fe2O3 content of the alumino-ferrocement components is 6% to 10%, and the Al2O3 content is 18% to 22%.

[0023] Preferably, the internal-cured nano-plant fiber emulsion contains internal-cured nano-plant fibers, and the internal-cured nano-plant fibers are one of nano-cellulose fibers or nano-lignin fibers, and the diameter of the internal-cured nano-plant fibers is 5 to 50 nm, and the length is 500 to 1000 nm.

[0024] Compared with the prior art, the early-strength corrosion-resistant ferroaluminate cement-based concrete and the preparation method thereof of the present invention have the following beneficial effects:

[0025] 1. The temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive collapse-preserving polycarboxylate water-reducing agent added to the early-strength corrosion-resistant ferroaluminate cement-based concrete of the present invention have an alkaneamine amide temperature-sensitive functional group in the molecular structure, a hydrophilic amide group (-CONH-) and a hydrophobic alkaneamine group [-CH2CR2NH2CH3], and exhibit different hydrophilic and hydrophobic properties at low temperatures (≤37°C) and high temperatures (>37°C). Traditional ferroaluminate cement concrete hydrates quickly at an early stage, releasing a large amount of heat, causing the concrete to heat up quickly. When ordinary polycarboxylate water-reducing agent is used, it is easy to cause it to be quickly adsorbed on the surface of cement particles, resulting in a rapid loss of concrete fluidity. The thermosensitive water-reducing polycarboxylate water-reducing agent used in this scheme can change the hydrophilicity of the thermosensitive functional group under high temperature conditions, reduce the adsorption rate of the water-reducing agent on the surface of cement particles, retain part of the water-reducing agent in the concrete slurry, and exert the long-lasting dispersion and retention effect of the water-reducing agent. In addition, the thermosensitive water-reducing polycarboxylate water-reducing agent and the thermosensitive slump-retaining water-reducing agent are used in combination to form a thermosensitive water-reducing agent with different adsorption rates in concrete under high temperature conditions. Since the thermosensitive slump-retaining water-reducing agent has not only a thermosensitive functional group in its molecular structure, but also a slow-release functional ester functional group, it has a lower adsorption rate than the thermosensitive water-reducing agent and ferroaluminate cement, and can maintain longer fluidity retention, which is conducive to solving the problem of rapid loss of concrete fluidity caused by concentrated heat release in the early stage of ferroaluminate cement concrete.

[0026] 2. The molecular structure of temperature-sensitive water-reducing polycarboxylic acid water-reducing agent and temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent contains alkane amino amide temperature-sensitive functional groups, which are hydrolyzed in the strong alkaline environment of concrete to form saturated alkane diamine groups. Due to its two amino structures, it has excellent early strength properties and can promote the early strength growth of ferroaluminate cement concrete.

[0027] 3. Aiming at the problems that alumina-ferrocement and common polycarboxylic acid high-performance water-reducing agent have poor compatibility and are prone to high cohesion, the present invention adopts two different types of air-entraining agents, rosin soap and fatty alcohol sulfonate, which can better maintain the stability of the internal air content of alumina-ferrocement concrete, help maintain the workability of concrete, reduce the viscosity of alumina-ferrocement concrete, and facilitate the construction of alumina-ferrocement concrete.

[0028] 4. The present invention prepares the early-strength and corrosion-resistant alumina ferrocement-based concrete by selecting low-heat alumina ferrocement and adding mineral admixtures to prepare low-hydration heat alumina ferrocement cement concrete; in addition, the present invention also adds internal curing nano-plant fiber emulsion, which can significantly improve the crack resistance of alumina ferrocement cement concrete and greatly reduce the risk of cracking of alumina ferrocement cement concrete through internal curing and fiber toughening effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 The synthetic process diagram of the (temperature-sensitive functional monomer) unsaturated alkane amino amide intermediate of this scheme, wherein R1 is H or CH3, and R2 is H or CH2CH3;

[0031] Figure 2 The molecular structure diagram of the temperature-sensitive water-reducing polycarboxylate water-reducing agent in this scheme, wherein R1 is H or CH3, R2 is H or CH2CH3, and m=45-55;

[0032] Figure 3 The molecular structure diagram of the temperature-sensitive water-reducing polycarboxylic acid water-reducing agent in this scheme, wherein R1 is H or CH3, R2 is H or CH2CH3, n=1 or 2, and m=45-55.

[0033] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0036] The present invention also provides a method for preparing early-strength corrosion-resistant ferroaluminate cement-based concrete, comprising the following preparation steps:

[0037] S01. According to weight, 280 to 400 parts of ferroaluminate cement, 0 to 70 parts of fly ash, 0 to 85 parts of mineral powder, 0 to 20 parts of silica fume, 670 to 750 parts of sand, and 1100 to 1150 parts of crushed stone are mixed in a concrete mixer and stirred for 10 to 15 seconds to obtain a premix;

[0038] S02. According to weight, 3 to 6 parts of special water reducer for ferroaluminate cement concrete and 0.6 to 1.2 parts of internal curing nano-plant fiber emulsion are added to 150 to 165 parts of water and mixed evenly, and then added to the premix of the concrete mixer and stirred for about 2 minutes to obtain the early strength and corrosion-resistant ferroaluminate cement-based concrete.

[0039] Among them, the strength grade of the ferroaluminate cement is not less than 42.5; in terms of mass percentage, the Fe2O3 content in the components of the ferroaluminate cement is 6% to 10%, and the Al2O3 content is 18% to 22%; the internally cured nano-plant fiber emulsion (solid content is 3%) contains internally cured nano-plant fibers and water (solution component), and the internally cured nano-plant fibers are one of nano-cellulose fibers or nano-lignin fibers, and the diameter of the internally cured nano-plant fibers is 5 to 50 nm, and the length is 500 to 1000 nm.

[0040] The fly ash in step S01 may be of grade II, the mineral powder may be of grade S95, and the specific surface area of ​​the silicon powder may be not less than 15000m 2 / kg, water requirement ratio is not more than 125%, and 28d activity index is not less than 115%. The sand can be one of river sand or machine-made sand, with a fineness modulus of 2.5-3.1, wherein the MB value of machine-made sand is ≤1.0, the stone powder content is ≤10.0%, and the flaky particle content is ≤5.0%; the crushed stone can be pebbles or shaped crushed stone, double-graded, triple-graded or continuously graded aggregate, and the close-packed void ratio is 35.0-37.0%; the water can be tap water or groundwater, and its performance meets the "Standard for Water Used in Concrete" (JGJ63).

[0041] Furthermore, the special water reducer for ferroaluminate cement concrete includes the following raw materials by weight: 8-12 parts of thermosensitive water-reducing polycarboxylic acid water reducer, 8-12 parts of thermosensitive slump-retaining polycarboxylic acid water reducer, 0-6 parts of retarder, 70-84 parts of water, 0.02-0.05 parts of defoamer, 0.02-0.06 parts of air entraining agent and 0.1-0.2 parts of preservative. Among them, the retarder is one or two of sodium gluconate, boric acid, citric acid or sodium phosphate; the defoamer is a polyether defoamer or a silicone defoamer; the air entraining agent is a mixture of rosin soap air entraining agent and fatty alcohol sulfonate air entraining agent in a weight ratio of 1:0.5-2; the preservative is an isothiazolinone preservative.

[0042] Furthermore, the preparation steps of the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive collapse-retaining polycarboxylate water-reducing agent include:

[0043] S1. Preparation of unsaturated alkane amino amide intermediate: 74 to 102 parts of saturated alkane diamine and 13.5 to 17.5 parts of water-carrying agent are sequentially added to the reactor and mixed and stirred evenly, the stirring speed is controlled at 25 to 40 r / min, and then 0.75 to 1.00 parts of catalyst are added, vacuum is evacuated and the air pressure is controlled to be below -0.09 MPa, the air tightness of the reaction device is checked, and then the temperature is raised to 90 to 105 ° C, 75 to 90 parts of unsaturated carboxylic acid are added in 3 times, and 1 / 3 of the total amount of unsaturated carboxylic acid is added every 1.5 hours until the addition is completed, and then the temperature is kept for 2 to 4 hours until no water comes out of the water separator, and the temperature is lowered to below 40 ° C. 37 to 48 parts of a 5 to 10% sodium bicarbonate solution are added to terminate the amidation reaction to obtain an unsaturated alkane amino amide intermediate;

[0044] S2. Preparation of a thermosensitive water-reducing polycarboxylate water reducer: 24 to 26 parts of the unsaturated alkane amino amide intermediate, 235 to 245 parts of a polyoxyethylene ether macromonomer and 10 to 20 parts of water are sequentially added to a reactor, mixed and stirred evenly, the stirring speed is controlled at 25 to 40 r / min, the temperature is raised to 30 to 60 ° C, 14 to 16 parts of an oxidant are added, and then liquid A and liquid B are sequentially added dropwise thereto, and finally 13 to 15 parts of a sodium hydroxide solution having a concentration of 28 to 35% is added, and the pH value is adjusted to 6.0 to 7.0 to obtain a thermosensitive water-reducing polycarboxylate water reducer;

[0045] S3. Preparation of a temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent: 25 to 26 parts of the unsaturated alkane amino amide intermediate, 240 to 250 parts of polyoxyethylene ether macromonomer and 20 to 30 parts of water are sequentially added into a reaction kettle, stirred evenly after mixing, the stirring speed is controlled at 25 to 40 r / min, the temperature is raised to 30 to 60°C, 15-16 parts of an oxidant is added, and then liquid A and liquid B are sequentially added dropwise thereto, and finally 15 to 16 parts of a sodium hydroxide solution having a concentration of 28 to 35% is added, and the pH value is adjusted to 6.0 to 7.0 to obtain a temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent.

[0046] The saturated alkane diamine is one of 1,2-propylene diamine and 2-methyl-1,2-butane diamine; the unsaturated carboxylic acid is one of acrylic acid and methacrylic acid; the water-carrying agent is cyclohexane; and the catalyst is one of concentrated sulfuric acid and p-toluenesulfonic acid.

[0047] In step S2 or step S3, the polyoxyethylene ether macromonomer is one of allyl polyoxyethylene ether (HPEG) or methyl allyl polyoxyethylene ether (TPEG); the oxidant is one of hydrogen peroxide or ammonium persulfate;

[0048] In step S2, the liquid A is composed of 18 to 22 parts of unsaturated carboxylic acid and 15 to 20 parts of water by weight; the liquid B is composed of 0.4 to 0.5 parts of reducing agent, 1.5 to 3 parts of chain transfer agent and 30 to 40 parts of water by weight, and the time for completing the dropwise addition of the liquid A is 2 to 3 hours, and the time for completing the dropwise addition of the liquid B is 2.5 to 3.5 hours;

[0049] In step S3, the liquid A is composed of 10 to 12 parts of unsaturated carboxylic acid, 35 to 39 parts of collapse-preserving functional monomers and 40 to 50 parts of water, by weight; the liquid B is composed of 0.4 to 0.5 parts of reducing agent, 2 to 3 parts of chain transfer agent and 30 to 40 parts of water, by weight, and the time for completing the dropwise addition of the liquid A is 2 to 3 hours, and the time for completing the dropwise addition of the liquid B is 2.5 to 3.5 hours;

[0050] In step S2 or step S3, the unsaturated carboxylic acid is one of acrylic acid or methacrylic acid; the reducing agent is vitamin C; the chain transfer agent is one of thioglycolic acid or thiopropionic acid; in step S3, the collapse-preserving functional monomer is one of hydroxyethyl acrylate or hydroxypropyl acrylate.

[0051] In summary, this scheme prepares concrete by adding special water reducer and internal curing materials to ferroaluminate cement, and synergistically regulates the hydration of ferroaluminate cement and the adsorption of admixtures, which can not only improve the workability of ferroaluminate cement concrete and reduce the viscosity of concrete; it can also improve the time retention of concrete slump, reduce its early hydration heat, and enhance the early mechanical properties, crack resistance and durability of concrete. It can be widely used in marine infrastructure projects such as ports, docks, and cross-sea bridges.

[0052] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0053] Example 1

[0054] First, a temperature-sensitive water-reducing polycarboxylate water-reducing agent and a temperature-sensitive collapse-retaining polycarboxylate water-reducing agent are prepared, comprising the following steps:

[0055] S1. First, prepare the unsaturated alkane amino amide intermediate. Add 74 parts of 1,2-propylenediamine and 13.5 parts of cyclohexane to the reactor in sequence, start stirring, and control the stirring speed at 25-40r / min, then add 0.75 parts of concentrated sulfuric acid, evacuate and control the air pressure to below -0.09MPa, check the air tightness of the reaction device, then heat to 90°C, add 75 parts of acrylic acid in 3 times, add 25 parts of acrylic acid every 1.5h until it is added, then keep warm for 4h until no water comes out of the water separator; cool to below 40°C, add 37 parts of 5% baking soda solution, terminate the amidation reaction, and finally obtain the unsaturated alkane amino amide intermediate.

[0056] S2. Preparation of a thermosensitive water-reducing polycarboxylic acid water reducer. 24 parts of the unsaturated alkane amino amide intermediate, 235 parts of HPEG polyether macromonomer and 10 parts of water are sequentially added to a reactor, stirring is started, the stirring speed is controlled at 25r / min, and the mixture is stirred evenly, the temperature is raised to 30°C, and 14 parts of a 30% hydrogen peroxide solution are added; then liquid A (18 parts of acrylic acid, 15 parts of water) is added dropwise for 2 hours, and liquid B (0.4 parts of vitamin C, 1.5 parts of thioglycolic acid and 30 parts of water) is added dropwise for 2.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 13 parts of a 28% sodium hydroxide solution is added, and the pH value is adjusted to 6.0 to obtain a thermosensitive water-reducing polycarboxylic acid water reducer.

[0057] S3. Preparation of a thermosensitive collapse-preserving polycarboxylic acid water reducer. 25 parts of the unsaturated alkane amino amide intermediate, 240 parts of HPEG polyether macromonomer and 20 parts of water are sequentially added to a reaction kettle, stirring is started, the stirring speed is controlled at 25r / min, and the mixture is stirred evenly, the temperature is raised to 30°C, and 15 parts of a 30% hydrogen peroxide solution are added; then liquid A (10 parts of acrylic acid, 35 parts of hydroxyethyl acrylate, and 40 parts of water) is added dropwise for 2 hours, and liquid B (0.4 parts of vitamin C, 2 parts of thioglycolic acid and 30 parts of water) is added dropwise for 2.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 15 parts of a 28% sodium hydroxide solution is added, and the pH value is adjusted to 6.0 to obtain a thermosensitive collapse-preserving polycarboxylic acid water reducer.

[0058] Then, a special water reducing agent for ferroaluminate cement concrete is prepared, which comprises the following steps:

[0059] Add 8 parts of thermosensitive water-reducing polycarboxylic acid water-reducing agent, 8 parts of thermosensitive collapse-retaining polycarboxylic acid water-reducing agent, 84 parts of water, 3 parts of sodium gluconate, 0.02 parts of polyether defoaming agent, 0.01 parts of rosin soap air-entraining agent, 0.01 parts of fatty alcohol sulfonate air-entraining agent and 0.1 parts of preservative into a stirring tank and stir for 0.5h to obtain a special water-reducing agent for ferroaluminate cement concrete.

[0060] Finally, the early strength and corrosion resistant ferroaluminate cement-based concrete is prepared, comprising the following steps:

[0061] S01. By weight, 280 parts of ferroaluminate cement, 70 parts of fly ash, 0 parts of mineral powder, 0 parts of silica fume, 750 parts of river sand, 220 parts of 5-10 mm gravel and 880 parts of 10-25 mm gravel were added to a concrete mixer and stirred for 10 seconds to obtain a premix;

[0062] S02. Add 3 parts of special water reducer for ferroaluminate cement concrete and 0.6 parts of internal curing nanocellulose fiber emulsion (diameter 20nm, length 500nm, aspect ratio 25:1) into 160 parts of water and disperse them, then add them to the premix in the concrete mixer and stir for 2 minutes to obtain C30 early strength and corrosion resistant ferroaluminate cement-based concrete.

[0063] Example 2

[0064] First, a temperature-sensitive water-reducing polycarboxylate water-reducing agent and a temperature-sensitive collapse-retaining polycarboxylate water-reducing agent are prepared, comprising the following steps:

[0065] S1. First, prepare the unsaturated alkane amino amide intermediate. Add 102 parts of 2-methyl-1,2-butanediamine and 17.5 parts of cyclohexane to the reactor in sequence, start stirring, control the stirring speed at 40r / min, then add 1.0 part of concentrated sulfuric acid, evacuate and control the air pressure to below -0.09MPa, check the air tightness of the reaction device, then heat to 105°C, add 90 parts of methacrylic acid in 3 times, add 30 parts of methacrylic acid every 1.5h until it is added, then keep warm for 4h until no water comes out of the water separator; cool to below 40°C, add 44 parts of 10% baking soda solution, terminate the amidation reaction, and finally obtain the unsaturated alkane amino amide intermediate.

[0066] S2. Preparation of a thermosensitive water-reducing polycarboxylic acid water reducer. 24 parts of the unsaturated alkane amino amide intermediate, 245 parts of TPEG polyether macromonomer and 20 parts of water are sequentially added to a reaction kettle, stirring is started, the stirring speed is controlled at 40r / min, and the mixture is stirred evenly, the temperature is raised to 60°C, and 16 parts of ammonium persulfate are added; then liquid A (22 parts of methacrylic acid, 15 parts of water) is added dropwise for 2 hours, and liquid B (0.4 parts of vitamin C, 1.5 parts of thioglycolic acid and 30 parts of water) is added dropwise for 2.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 13 parts of 35% sodium hydroxide solution is added, and the pH value is adjusted to 6.8 to obtain a thermosensitive water-reducing polycarboxylic acid water reducer.

[0067] S3. Preparation of a thermosensitive collapse-preserving polycarboxylic acid water reducer. 26 parts of the unsaturated alkane aminoamide intermediate, 250 parts of HPEG polyether macromonomer and 30 parts of water are sequentially added to a reaction kettle, stirring is started, the stirring speed is controlled at 40r / min, and the mixture is stirred evenly, the temperature is raised to 60°C, and 16 parts of ammonium persulfate are added; then liquid A (12 parts of methacrylic acid, 39 parts of hydroxypropyl acrylate, and 50 parts of water) is added dropwise for 3 hours, and liquid B (0.5 parts of vitamin C, 3 parts of mercaptopropionic acid and 40 parts of water) is added dropwise for 2.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 16 parts of 35% sodium hydroxide solution are added, and the pH value is adjusted to 6.5 to obtain a thermosensitive collapse-preserving polycarboxylic acid water reducer.

[0068] Then, a special water reducing agent for ferroaluminate cement concrete is prepared, which comprises the following steps:

[0069] Add 12 parts of thermosensitive water-reducing polycarboxylic acid water-reducing agent, 12 parts of thermosensitive collapse-retaining polycarboxylic acid water-reducing agent, 76 parts of water, 2 parts of sodium gluconate, 0.05 parts of silicone defoaming agent, 0.03 parts of rosin soap air-entraining agent, 0.03 parts of fatty alcohol sulfonate air-entraining agent and 0.2 parts of preservative into a stirring tank and stir for 0.5h to obtain a special water-reducing agent for ferroaluminate cement concrete.

[0070] Finally, the early strength and corrosion resistant ferroaluminate cement-based concrete is prepared, comprising the following steps:

[0071] S01. By weight, 400 parts of ferroaluminate cement, 0 parts of fly ash, 80 parts of mineral powder, 0 parts of silica fume, 670 parts of river sand, 345 parts of 5-10mm gravel, 805 parts of 10-25mm gravel were added to a concrete mixer and stirred for 10s to obtain a premix;

[0072] S02. Add 6 parts of special water reducer for ferroaluminate cement concrete and 1.2 parts of internal curing nano-lignin fiber emulsion (diameter 5nm, length 500nm, aspect ratio 100:1) into 150 parts of water and disperse them, then add them to the premix of the concrete mixer and stir for 2 minutes to obtain C60 early strength and corrosion-resistant ferroaluminate cement-based concrete.

[0073] Example 3

[0074] First, a temperature-sensitive water-reducing polycarboxylate water-reducing agent and a temperature-sensitive collapse-retaining polycarboxylate water-reducing agent are prepared, comprising the following steps:

[0075] S1. First, prepare the unsaturated alkane amino amide intermediate. Add 74 parts of 1,2-propylenediamine and 15 parts of cyclohexane to the reactor in sequence, start stirring, control the stirring speed at 30r / min, then add 0.85 parts of concentrated sulfuric acid, evacuate and control the air pressure to below -0.09MPa, check the air tightness of the reaction device, then heat to 100°C, add 90 parts of methacrylic acid in 3 times, add 30 parts of methacrylic acid every 1.5h until it is added, then keep warm for 3h until no water comes out of the water separator; cool to below 40°C, add 41 parts of 7% baking soda solution, terminate the amidation reaction, and finally obtain the unsaturated alkane amino amide intermediate.

[0076] S2. Preparation of thermosensitive water-reducing polycarboxylic acid water reducer. 25 parts of the unsaturated alkane amino amide intermediate, 240 parts of HPEG polyether macromonomer and 15 parts of water are added to the reactor in sequence, stirring is started, the stirring speed is controlled at 30r / min, and the mixture is stirred evenly, and the temperature is raised to 40°C and 15 parts of 30% hydrogen peroxide solution are added. Then liquid A (19 parts of acrylic acid, 18 parts of water) is added dropwise for 2.5 hours, and liquid B (0.45 parts of vitamin C, 2 parts of thioglycolic acid and 35 parts of water) is added dropwise for 3.0 hours, and liquid A and liquid B are controlled to be added dropwise at a uniform speed; finally, 14 parts of 30% sodium hydroxide solution is added, and the pH value is adjusted to 7.0 to obtain a thermosensitive water-reducing polycarboxylic acid water reducer.

[0077] S3. Preparation of a thermosensitive collapse-preserving polycarboxylic acid water reducer. 25 parts of the unsaturated alkane amino amide intermediate, 245 parts of HPEG polyether macromonomer and 25 parts of water are sequentially added to a reactor, stirring is started, the stirring speed is controlled at 30 r / min, and the mixture is stirred evenly, the temperature is raised to 40°C, and 15.5 parts of a 30% hydrogen peroxide solution is added; then liquid A (10 parts of acrylic acid, 39 parts of hydroxypropyl acrylate, and 45 parts of water) is added dropwise for 2.5 hours, and liquid B (0.45 parts of vitamin C, 2.5 parts of thioglycolic acid and 35 parts of water) is added dropwise for 3.0 hours, and liquids A and B are added dropwise at a uniform speed; finally, 15.5 parts of a 30% sodium hydroxide solution is added, and the pH value is adjusted to 7.0 to obtain a thermosensitive collapse-preserving polycarboxylic acid water reducer.

[0078] Then, a special water reducing agent for ferroaluminate cement concrete is prepared, which comprises the following steps:

[0079] Add 10 parts of thermosensitive water-reducing polycarboxylic acid water-reducing agent, 10 parts of thermosensitive collapse-retaining polycarboxylic acid water-reducing agent, 76 parts of water, 2 parts of boric acid, 2 parts of sodium gluconate, 0.04 parts of polyether defoaming agent, 0.02 parts of rosin soap air-entraining agent, 0.01 parts of fatty alcohol sulfonate air-entraining agent and 0.15 parts of preservative into a stirring tank and stir for 0.5h to obtain a special water-reducing agent for ferroaluminate cement concrete.

[0080] Finally, the early strength and corrosion resistant ferroaluminate cement-based concrete is prepared, comprising the following steps:

[0081] S01. By weight, 315 parts of ferroaluminate cement, 0 parts of fly ash, 85 parts of mineral powder, 20 parts of silica fume, 690 parts of machine-made sand, 340 parts of 5-10 mm gravel, 790 parts of 10-25 mm gravel were added to a concrete mixer and stirred for 10 seconds to obtain a premix;

[0082] S02. Add 5 parts of special water reducer for ferroaluminate cement concrete and 1.0 part of internal curing nanocellulose fiber emulsion (diameter 50nm, length 1000nm, aspect ratio 20:1) into 160 parts of water and disperse them, then add them into the premix of the concrete mixer and stir for 2 minutes to obtain C40 early strength and corrosion resistant ferroaluminate cement-based concrete.

[0083] Example 4

[0084] First, a temperature-sensitive water-reducing polycarboxylate water-reducing agent and a temperature-sensitive collapse-retaining polycarboxylate water-reducing agent are prepared, comprising the following steps:

[0085] S1. First, prepare the unsaturated alkane amino amide intermediate. Add 102 parts of 2-methyl-1,2-butanediamine and 16 parts of cyclohexane to the reactor in sequence, start stirring, control the stirring speed at 35r / min, then add 0.9 parts of concentrated sulfuric acid, evacuate and control the air pressure to below -0.09MPa, check the air tightness of the reaction device, then heat to 95°C, add 75 parts of acrylic acid in 3 times, add 25 parts of acrylic acid every 1.5h until it is added, then keep warm for 4h until no water comes out of the water separator; cool to below 40°C, add 44 parts of 5% baking soda solution, terminate the amidation reaction, and finally obtain the unsaturated alkane amino amide intermediate.

[0086] S2. Preparation of a thermosensitive water-reducing polycarboxylic acid water-reducing agent. 24 parts of the unsaturated alkane amino amide intermediate, 240 parts of TPEG polyether macromonomer and 15 parts of water are sequentially added to a reactor, stirring is started, the stirring speed is controlled at 35r / min, and the mixture is stirred evenly, the temperature is raised to 50°C, and 15 parts of a 30% hydrogen peroxide solution are added; then liquid A (21 parts of methacrylic acid, 19 parts of water) is added dropwise for 3.0 hours, and liquid B (0.5 parts of vitamin C, 2.5 parts of mercaptopropionic acid and 38 parts of water) is added dropwise for 3.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 14.5 parts of a 28% sodium hydroxide solution is added, and the pH value is adjusted to 6.5 to obtain a thermosensitive water-reducing polycarboxylic acid water-reducing agent.

[0087] S3. Preparation of a thermosensitive collapse-preserving polycarboxylic acid water reducer. 25.5 parts of the unsaturated alkane aminoamide intermediate, 240 parts of TPEG polyether macromonomer and 30 parts of water are sequentially added to a reactor, stirring is started, the stirring speed is controlled at 35r / min, and the mixture is stirred evenly, the temperature is raised to 50°C, and 15.5 parts of a 30% hydrogen peroxide solution is added; then liquid A (12 parts of methacrylic acid, 35 parts of hydroxyethyl acrylate, and 43 parts of water) is added dropwise for 3.0 hours, and liquid B (0.46 parts of vitamin C, 2.4 parts of thioglycolic acid and 37 parts of water) is added dropwise for 3.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 16.0 parts of a 28% sodium hydroxide solution is added, and the pH value is adjusted to 6.0 to obtain a thermosensitive collapse-preserving polycarboxylic acid water reducer.

[0088] Then, a special water reducing agent for ferroaluminate cement concrete is prepared, which comprises the following steps:

[0089] Add 9 parts of thermosensitive water-reducing polycarboxylic acid water-reducing agent, 9 parts of thermosensitive collapse-retaining polycarboxylic acid water-reducing agent, 76 parts of water, 2 parts of citric acid, 3 parts of sodium phosphate, 0.03 parts of polyether defoaming agent, 0.02 parts of rosin soap air-entraining agent, 0.03 parts of fatty alcohol sulfonate air-entraining agent, and 0.2 parts of preservative into a stirring tank and stir for 0.5h to obtain a special water-reducing agent for ferroaluminate cement concrete.

[0090] Finally, the early strength and corrosion resistant ferroaluminate cement-based concrete is prepared, comprising the following steps:

[0091] S01. By weight, 285 parts of ferroaluminate cement, 57 parts of fly ash, 38 parts of mineral powder, 0 parts of silica fume, 695 parts of machine-made sand, 340 parts of 5-10 mm gravel, 800 parts of 10-25 mm gravel were added to a concrete mixer and stirred for 10 seconds to obtain a premix;

[0092] S02. Add 4.5 parts of special water reducer for ferroaluminate cement concrete and 0.9 parts of internal curing nano-lignin fiber emulsion (diameter 30nm, length 900nm, aspect ratio 30:1) into 165 parts of water and disperse them, then add them to the premix of the concrete mixer and stir for 2 minutes to obtain C35 early strength and corrosion-resistant ferroaluminate cement-based concrete.

[0093] Comparative Example 1

[0094] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that: when preparing ferroaluminate cement-based concrete, a traditional silicate cement concrete water reducer is used instead of the ferroaluminate cement concrete water reducer of this scheme (i.e., a temperature-sensitive water-reducing type and a slump-retaining polycarboxylate water reducer are not used).

[0095] Specifically, the preparation of ferroaluminate cement-based concrete includes the following steps:

[0096] S01. Add 280 parts of ferroaluminate cement, 70 parts of fly ash, 0 parts of mineral powder, 0 parts of silica fume, 750 parts of river sand, 220 parts of 5-10mm gravel, 880 parts of 10-25mm gravel into a concrete mixer by weight and stir for 10s;

[0097] S02. Add 3 parts of silicate cement concrete water reducer and 0.6 parts of internal curing nanocellulose fiber emulsion into 160 parts of water and disperse them, then add them into a concrete mixer and stir for 2 minutes to prepare C30 ferroaluminate cement-based concrete.

[0098] Comparative Example 2

[0099] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that: when preparing the temperature-sensitive water-reducing polycarboxylic acid water-reducing agent and the collapse-retaining polycarboxylic acid water-reducing agent, the unsaturated alkane amino amide intermediate is not prepared, and N-isopropyl acrylamide is directly used to replace the unsaturated alkane amino amide intermediate.

[0100] Comparative Example 3

[0101] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that the water reducer for ferroaluminate cement concrete adopts a temperature-sensitive water-reducing polycarboxylic acid water reducer and a common slump-retaining water reducer, and the common slump-retaining water reducer is used instead of the temperature-sensitive slump-retaining water reducer.

[0102] Comparative Example 4

[0103] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that the internal curing nanocellulose fiber emulsion is not added in the preparation of the ferroaluminate cement concrete.

[0104] Comparative Example 5

[0105] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that: as the raw material of the water reducer for ferroaluminate cement concrete, only the temperature-sensitive water-reducing polycarboxylate water reducer is added, and the temperature-sensitive collapse-preserving polycarboxylate water reducer is not added.

[0106] Comparative Example 6

[0107] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that: as the raw material of the water reducer for ferroaluminate cement concrete, only the temperature-sensitive collapse-preserving polycarboxylate water reducer is added, and no temperature-sensitive water-reducing polycarboxylate water reducer is added.

[0108] Comparative Example 7

[0109] The preparation steps and parameters in this comparative example are the same as those in Example 1, except that when preparing the special water reducer for ferroaluminate cement concrete, only 0.02 parts of one air entraining agent, fatty alcohol sulfonate air entraining agent, is added.

[0110] The performance of the early-strength and corrosion-resistant alumina-ferrocement-based concrete prepared in Examples 1-4 and Comparative Examples 1-7 was tested, and the test results are shown in the following table:

[0111] Table 1 Basic physical and mechanical properties of ferroaluminate cement concrete

[0112]

[0113]

[0114] It can be seen from the test results in Table 1 that the early-strength corrosion-resistant ferroaluminate cement-based concrete prepared in Examples 1 to 4 of the present invention has good workability, and the slump loss of concrete is small after 1 hour; the early strength is high, and the compressive strength of the concrete at 3 days has reached the corresponding concrete strength grade, and the compressive strength of the concrete at 28 days has increased significantly; in addition, the concrete has good durability, and the electric flux at either 3 days or 28 days is not greater than 300C, which can be applied to marine infrastructure concrete structures such as ports, docks, and cross-sea bridges.

[0115] Comparative Example 1 Compared with Example 1, the water reducer for silicate cement concrete is used instead of the water reducer for ferroaluminate cement concrete in this scheme. The prepared concrete has poor workability, is relatively sticky as a whole, and has a large slump loss over time; compared with Example 1, the early strength adiabatic temperature rise of the concrete increases, indicating that the water reducer for silicate cement concrete is used in ferroaluminate cement concrete, and has little effect on delaying the hydration of cement; the compressive strength and durability (electric flux) of the concrete are worse than those in Example 1.

[0116] Comparative Example 2 Compared with Example 1, N-isopropyl acrylamide is used to replace the unsaturated alkane amino amide intermediate, and the hydration exothermic temperature of the ferroaluminate cement concrete is suppressed to be higher than that of Example 1, the slump loss over time is greater, and the mechanical properties and durability are worse than those of Example 1. It is explained that the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the slump-retaining polycarboxylate water-reducing agent prepared by using the temperature-sensitive functional monomer unsaturated alkane amino amide intermediate of the present invention have better adaptability to ferroaluminate cement concrete.

[0117] Compared with Example 1, Comparative Example 3 only uses a temperature-sensitive water-reducing type water-reducing agent. When the temperature-sensitive slump-retaining type water-reducing agent is replaced by an ordinary slump-retaining type water-reducing agent, the slump loss of the concrete in 1 hour is large, but compared with Comparative Example 1 using ordinary water-reducing type and slump-retaining type water-reducing agents, the slump loss of the concrete in 1 hour is reduced; in addition, the thermal insulation temperature rise of the concrete in Comparative Example 3 is higher than that in Example 1, the compressive strength is lower than that in Example 1, and the electric flux is higher than that in Example 1.

[0118] Comparative Example 4 Compared with Example 1, when preparing ferroaluminate cement concrete without adding internal curing nanocellulose fiber emulsion, the cohesion of concrete will be deteriorated, the thermal insulation temperature rise of concrete will be slightly increased, the compressive strength will be slightly reduced, and the electric flux will be slightly increased. It shows that the internal curing nanocellulose fiber emulsion can improve the cohesion of ferroaluminate cement concrete, enhance the mechanical properties and electric flux properties of concrete, and because the internal curing nanocellulose fiber emulsion has the functions of internal curing and fiber toughening, it can further enhance the crack resistance of ferroaluminate cement concrete.

[0119] Comparative Example 5 Compared with Example 1, the raw materials of the water-reducing agent for ferroaluminate cement concrete only add the temperature-sensitive water-reducing polycarboxylate water-reducing agent, and no temperature-sensitive slump-retaining polycarboxylate water-reducing agent is added. The initial workability of the concrete is good, but the slump loss is large, the adiabatic temperature rise of the concrete is reduced, the compressive strength is reduced, and the electric flux is increased. It shows that the addition of the temperature-sensitive slump-retaining polycarboxylate water-reducing agent alone causes a large slump loss of the concrete, which is not conducive to on-site concrete construction.

[0120] Comparative Example 6 Compared with Example 1, the raw materials of the water-reducing agent for ferroaluminate cement concrete only add the thermosensitive slump-retaining polycarboxylate water-reducing agent, and no thermosensitive water-reducing polycarboxylate water-reducing agent is added. The initial workability of the concrete is good, but the initial fluidity is general. Compared with Example 1, the slump loss is still large, the thermal insulation temperature rise of the concrete increases, the compressive strength increases, and the electric flux decreases. It shows that when only the thermosensitive slump-retaining polycarboxylate water-reducing agent is added, the concrete has poor fluidity out of the machine and a large slump loss, which is not conducive to on-site concrete construction. Comprehensive comparison of Examples 3, 5 and 6 shows that for ferroaluminate cement concrete, the thermosensitive water-reducing polycarboxylate water-reducing agent and the thermosensitive slump-retaining polycarboxylate water-reducing agent of this scheme are compounded, and the time-retention performance of the concrete slump, the delayed hydration heat release, the mechanical properties and the electric flux performance are all stronger than the single thermosensitive water-reducing agent and the conventional slump-retaining water-reducing agent, the single thermosensitive water-reducing agent type and the single thermosensitive slump-retaining water-reducing agent.

[0121] Comparative Example 7 Compared with Example 1, when preparing a special water reducing agent for ferroaluminate cement concrete, only one air entraining agent, 0.02 parts of fatty alcohol sulfonate air entraining agent, was added. The workability of the concrete was slightly worse than that of Example 1, resulting in a slightly increased slump loss of the concrete, an increased adiabatic temperature rise of the concrete, a decreased strength, and an increased electric flux. This is mainly because the pores inside the concrete are unevenly distributed, resulting in a slight decrease in the strength of the concrete and a slight increase in the electric flux.

[0122] Example 5

[0123] The preparation steps and parameters in this embodiment are the same as those in Example 1, except that the weight ratios of the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive collapse-retaining polycarboxylate water-reducing agent are different, as shown in the following table:

[0124]

[0125] The performance of the early-strength corrosion-resistant alumina-ferrocement-based concrete prepared in Example 5 was tested, and the test results are shown in the following table:

[0126] Table 2 Basic physical and mechanical properties of ferroaluminate cement concrete

[0127]

[0128] It can be seen from the test results in Table 2 that, when preparing a special water reducer for ferroaluminate cement concrete, the present scheme further limits the weight ratio of the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive slump-retaining polycarboxylate water-reducing agent, specifically in the range of (8-11): (8-10), so that the slump retention, hydration heat release, compressive strength and electric flux performance of the prepared early-strength and corrosion-resistant ferroaluminate cement-based concrete can be improved. Among them, when the weights of the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive slump-retaining polycarboxylate water-reducing agent are 8 parts and 10 parts respectively, the performance of the prepared concrete is relatively optimal.

[0129] Example 6

[0130] The preparation steps and parameters in this embodiment are the same as those in embodiment 1, except that the parameters of the internally cured nanocellulose fibers in the internally cured nanocellulose fibers are different, as shown in the following table:

[0131]

[0132] The performance of the early-strength corrosion-resistant alumina-ferrocement-based concrete prepared in Example 6 was tested, and the test results are shown in the following table:

[0133] Table 3 Basic physical and mechanical properties of ferroaluminate cement concrete

[0134]

[0135]

[0136] It can be seen from the test results in Table 3 above that the internal curing nano-plant fiber emulsion used in this scheme is preferably a combination of two fibers, the weight ratio of nanocellulose fiber to nanolignin fiber is preferably (1-2): (1-2), and the aspect ratio of nanocellulose fiber is preferably limited to (30-40): 1, and the aspect ratio of nanolignin fiber is preferably limited to (20-25): 1, which can improve the slump retention, compressive strength and electric flux performance of the obtained early strength and corrosion-resistant ferroaluminate cement-based concrete. Among them, when the weight ratio of nanocellulose fiber (aspect ratio of 40: 1) and nanolignin fiber (aspect ratio of 20: 1) is 2: 1, the performance of the obtained concrete is relatively optimal.

[0137] Example 7

[0138] First, a temperature-sensitive water-reducing polycarboxylate water-reducing agent and a temperature-sensitive collapse-retaining polycarboxylate water-reducing agent are prepared, comprising the following steps:

[0139] S1. First, prepare the unsaturated alkane amino amide intermediate. Add 102 parts of 2-methyl-1,2-butanediamine and 16 parts of cyclohexane to the reactor in sequence, start stirring, and control the stirring speed at 35r / min, then add 0.9 parts of concentrated sulfuric acid, evacuate and control the air pressure to below -0.09MPa, check the air tightness of the reaction device, then heat to 105°C, add 75 parts of acrylic acid in 3 times, add 25 parts of acrylic acid every 1.5h until it is added, and then keep warm for 4h until no water comes out of the water separator; cool to below 40°C, add 44 parts of 5% baking soda solution, terminate the amidation reaction, and finally obtain the unsaturated alkane amino amide intermediate.

[0140] S2. Preparation of a thermosensitive water-reducing polycarboxylic acid water reducer. 24 parts of the unsaturated alkane amino amide intermediate, 240 parts of TPEG polyether macromonomer and 15 parts of water are sequentially added to a reactor, stirring is started, the stirring speed is controlled at 35r / min, and the mixture is stirred evenly, the temperature is raised to 40°C, and 15 parts of a 30% hydrogen peroxide solution are added; then liquid A (21 parts of methacrylic acid, 19 parts of water) is added dropwise for 3.0 hours, and liquid B (0.5 parts of vitamin C, 2.5 parts of mercaptopropionic acid and 38 parts of water) is added dropwise for 3.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 14.5 parts of a 28% sodium hydroxide solution is added, and the pH value is adjusted to 6.5 to obtain a thermosensitive water-reducing polycarboxylic acid water reducer.

[0141] S3. Preparation of a thermosensitive collapse-preserving polycarboxylic acid water reducer. 25.5 parts of the unsaturated alkane amino amide intermediate, 240 parts of TPEG polyether macromonomer and 30 parts of water are sequentially added to a reactor, stirring is started, the stirring speed is controlled at 35r / min, and the mixture is stirred evenly, the temperature is raised to 40°C, and 15.5 parts of a 30% hydrogen peroxide solution is added; then liquid A (12 parts of methacrylic acid, 35 parts of hydroxyethyl acrylate, and 43 parts of water) is added dropwise for 3.0 hours, and liquid B (0.46 parts of vitamin C, 2.4 parts of thioglycolic acid and 37 parts of water) is added dropwise for 3.5 hours, and liquids A and B are added dropwise at a uniform speed; finally, 16.0 parts of a 28% sodium hydroxide solution is added, and the pH value is adjusted to 6.5 to obtain a thermosensitive collapse-preserving polycarboxylic acid water reducer.

[0142] Then, a special water reducing agent for ferroaluminate cement concrete is prepared, which comprises the following steps:

[0143] Add 8 parts of thermosensitive water-reducing polycarboxylic acid water-reducing agent, 10 parts of thermosensitive collapse-retaining polycarboxylic acid water-reducing agent, 76 parts of water, 2 parts of sodium gluconate, 2 parts of sodium phosphate, 0.03 parts of polyether defoaming agent, 0.02 parts of rosin soap air-entraining agent, 0.02 parts of fatty alcohol sulfonate air-entraining agent, and 0.2 parts of preservative into a stirring tank and stir for 0.5h to obtain a special water-reducing agent for ferroaluminate cement concrete.

[0144] Finally, the early strength and corrosion resistant ferroaluminate cement-based concrete is prepared, comprising the following steps:

[0145] S01. By weight, 280 parts of ferroaluminate cement, 70 parts of fly ash, 0 parts of mineral powder, 0 parts of silica fume, 750 parts of river sand, 220 parts of 5-10 mm gravel and 880 parts of 10-25 mm gravel were added to a concrete mixer and stirred for 10 seconds to obtain a premix;

[0146] S02. Add 3 parts of special water reducer for ferroaluminate cement concrete and 0.6 parts of internal curing nanocellulose fiber emulsion (the weight ratio of nanocellulose fiber to nanolignin fiber is 2:1, the solid content is 3%, wherein the length of nanocellulose fiber is 1000nm, the diameter is 25nm, and the aspect ratio is 40:1; the length of nanolignin fiber is 500nm, the diameter is 25nm, and the aspect ratio is 20:1) into 160 parts of water and disperse them, then add them to the premix in the concrete mixer and stir for 2 minutes to obtain C30 early strength and corrosion-resistant ferroaluminate cement-based concrete.

[0147] The performance of the early-strength corrosion-resistant alumina-ferrocement-based concrete prepared in Example 7 was tested, and the test results are shown in the following table:

[0148] Table 4 Basic physical and mechanical properties of ferroaluminate cement concrete

[0149]

[0150] It can be seen from the test results in Table 4 above that after comprehensive optimization of raw materials, proportions and parameters of each raw material, the early-strength and corrosion-resistant ferroaluminate cement-based concrete has very good workability, and there is no loss in the slump of concrete after 1 hour; the early strength of the concrete is high, and the compressive strength of the concrete can reach 35.8MPa at 3d; the electric flux of the concrete can be reduced to below 260C at 3d or 28d, and it has excellent durability.

[0151] The above embodiments are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. The fluororana solution mentioned in the present invention is not limited to the above-mentioned ones, so the above embodiments cannot be regarded as limiting the protection scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. An early-strength, corrosion-resistant ferroaluminate cement-based concrete, characterized in that: The raw materials are as follows, measured in parts by weight: 280-400 parts of ferroaluminate cement, 0-70 parts of fly ash, 0-85 parts of mineral powder, 0-20 parts of silica fume, 670-750 parts of sand, 1100-1150 parts of crushed stone, 150-165 parts of water, 3-6 parts of special water reducer for ferroaluminate cement concrete and 0.6-1.2 parts of internal curing nano-plant fiber emulsion.

2. The early-strength, corrosion-resistant ferroaluminate cement-based concrete according to claim 1, characterized in that: The special water reducer for ferroaluminate cement concrete includes the following raw materials by weight: 8 to 12 parts of temperature-sensitive water-reducing polycarboxylic acid water reducer, 8 to 12 parts of temperature-sensitive slump-retaining polycarboxylic acid water reducer, 0 to 6 parts of retarder, 70 to 84 parts of water, 0.02 to 0.05 parts of defoamer, 0.02 to 0.06 parts of air entraining agent and 0.1 to 0.2 parts of preservative.

3. The early-strength corrosion-resistant ferroaluminate cement-based concrete according to claim 2, characterized in that: The preparation steps of the temperature-sensitive water-reducing polycarboxylate water-reducing agent and the temperature-sensitive collapse-retaining polycarboxylate water-reducing agent include: S1. Preparation of unsaturated alkane amino amide intermediate: 74 to 102 parts of saturated alkane diamine and 13.5 to 17.5 parts of water-carrying agent are mixed and stirred evenly, and then 0.75 to 1.00 parts of catalyst are added, and then the temperature is raised to 90 to 105° C., 75 to 90 parts of unsaturated carboxylic acid are added, and the temperature is kept for 2 to 4 hours until no water is generated, and the temperature is lowered to below 40° C. and 37 to 48 parts of baking soda solution with a concentration of 5 to 10% are added to terminate the amidation reaction to obtain an unsaturated alkane amino amide intermediate; S2. Preparation of a thermosensitive water-reducing polycarboxylate water reducer: 24 to 26 parts of the unsaturated alkane amino amide intermediate, 235 to 245 parts of a polyoxyethylene ether macromonomer and 10 to 20 parts of water were mixed and stirred evenly, heated to 30 to 60 ° C, 14 to 16 parts of an oxidant were added, and then solution A and solution B were added dropwise thereto in sequence, and finally 13 to 15 parts of a sodium hydroxide solution having a concentration of 28 to 35% was added, and the pH value was adjusted to 6.0 to 7.0 to obtain a thermosensitive water-reducing polycarboxylate water reducer; S3. Preparation of a temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent: 25 to 26 parts of the unsaturated alkane amino amide intermediate, 240 to 250 parts of polyoxyethylene ether macromonomer and 20 to 30 parts of water are mixed and stirred evenly, the temperature is raised to 30 to 60°C, 15-16 parts of an oxidant are added, and then liquid A and liquid B are added dropwise thereto in sequence, and finally 15 to 16 parts of a sodium hydroxide solution with a concentration of 28 to 35% are added, and the pH value is adjusted to 6.0 to 7.0 to obtain a temperature-sensitive collapse-retaining polycarboxylic acid water-reducing agent.

4. The early-strength, corrosion-resistant ferroaluminate cement-based concrete according to claim 3, characterized in that: In step S1, 75 to 90 parts of the unsaturated carboxylic acid are added in three portions, with 1 / 3 of the total amount of the unsaturated carboxylic acid added every 1.5 hours until the addition is complete; The saturated alkane diamine is one of 1,2-propylene diamine and 2-methyl-1,2-butane diamine; the unsaturated carboxylic acid is one of acrylic acid and methacrylic acid; the water-carrying agent is cyclohexane; and the catalyst is one of concentrated sulfuric acid and p-toluenesulfonic acid.

5. The early-strength corrosion-resistant ferroaluminate cement-based concrete according to claim 3, characterized in that: In step S2 or step S3, the polyoxyethylene ether macromonomer is one of allyl polyoxyethylene ether or methyl allyl polyoxyethylene ether; and the oxidant is one of hydrogen peroxide or ammonium persulfate.

6. The early-strength corrosion-resistant ferroaluminate cement-based concrete according to claim 3, characterized in that: In step S2, the liquid A is composed of 18 to 22 parts of unsaturated carboxylic acid and 15 to 20 parts of water by weight; the liquid B is composed of 0.4 to 0.5 parts of reducing agent, 1.5 to 3 parts of chain transfer agent and 30 to 40 parts of water by weight, and the time for completing the dropwise addition of the liquid A is 2 to 3 hours, and the time for completing the dropwise addition of the liquid B is 2.5 to 3.5 hours; In step S3, the liquid A is composed of 10 to 12 parts of unsaturated carboxylic acid, 35 to 39 parts of collapse-preserving functional monomers and 40 to 50 parts of water, by weight; the liquid B is composed of 0.4 to 0.5 parts of reducing agent, 2 to 3 parts of chain transfer agent and 30 to 40 parts of water, by weight, and the time for completing the dropwise addition of the liquid A is 2 to 3 hours, and the time for completing the dropwise addition of the liquid B is 2.5 to 3.5 hours; In step S2 or step S3, the unsaturated carboxylic acid is one of acrylic acid or methacrylic acid; the reducing agent is vitamin C; and the chain transfer agent is one of thioglycolic acid or thiopropionic acid; In step S3, the collapse-preserving functional monomer is one of hydroxyethyl acrylate and hydroxypropyl acrylate.

7. The early-strength, corrosion-resistant ferroaluminate cement-based concrete according to claim 2, characterized in that: The retarder is one or two of sodium gluconate, boric acid, citric acid or sodium phosphate; the defoamer is a polyether defoamer or a silicone defoamer; the air entraining agent is a mixture of a rosin soap air entraining agent and a fatty alcohol sulfonate air entraining agent in a weight ratio of 1:0.5-2; the preservative is an isothiazolinone preservative.

8. A method for preparing the early-strength corrosion-resistant ferroaluminate cement-based concrete according to any one of claims 1 to 7, characterized in that: The steps include: S01. Mix the ferroaluminate cement, the fly ash, the mineral powder, the silica fume, the sand and the gravel in parts by weight and stir for 10 to 15 seconds to obtain a premix; S02. According to weight, the special water reducer for alumina ferroaluminate cement concrete and the internal curing nano-plant fiber emulsion are added to water and mixed evenly, and then added to the premix and stirred evenly to obtain the early strength and corrosion-resistant alumina ferroaluminate cement-based concrete.

9. The method for preparing an early-strength corrosion-resistant ferroaluminate cement-based concrete according to claim 8, characterized in that: The strength grade of the alumino-ferrocement is not less than 42.5; in terms of mass percentage, the Fe2O3 content of the alumino-ferrocement is 6% to 10%, and the Al2O3 content is 18% to 22%.

10. The method for preparing an early-strength corrosion-resistant ferroaluminate cement-based concrete according to claim 8, characterized in that: The internal curing nano-plant fiber emulsion contains internal curing nano-plant fibers, which are nano-cellulose fibers or nano-lignin fibers. The diameter of the internal curing nano-plant fibers is 5 to 50 nm, and the length is 500 to 1000 nm.

Citation Information

Patent Citations

  • Method for synthesizing polycarboxylic acid high-property water reducer by copolymerization of amidated active monomers

    CN102181020A

  • High-performance concrete with high seawater corrosion resistance and preparation method thereof

    CN117185754A

  • High fluidity ultrahigh early-strength admixture and high fluidity ultrahigh early-strength concrete

    JP2009155184A

  • Surface-reinforced super-early-hardening cement concrete composition with improved durability and repairing method of concrete structure therewith

    KR101953106B1

  • Polycarboxylic acid water-reducing agent with high adaptability to temperature and method for preparing the same

    US20220041505A1